Should China revisit the 1994 fiscal reforms? - Ehtisham Ahmad (University of Bonn, Center for Development Research (ZEF), 2011)
The 1994 reforms in China were remarkably successful in stabilizing the economy and raising revenues for the benefit of sustainable growth and permitting the central government to redistribute resources to poorer regions through an equalization framework. However, the rise of informal local borrowing in the absence of effective own-source revenues raises possible risks and imbalances in the future. There is thus a need to reconsider the fundamentals of intergovernmental fiscal relations, building on the basis laid in the 1994 reforms.
Keywords: H2; H5; H6; H7; 330; Finanzreform; Finanzföderalismus; Finanzausgleich; China